1997
DOI: 10.1111/j.1600-0668.1997.t01-1-00007.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature on the Emission of Volatile Organic Compounds from PVC flooring, Carpet, and Paint

Abstract: The influence of temperature on the emission rate of volatile organic compounds (VOC) from four indoor materials was investigated in a small dynamic test chamber. The materials investigated were two carpets, a PVC flooring and a paint; the temperature range investigated was 23–50°C. The general trend was an increased initial emission rate and an increased decay rate with increasing temperature. The total emitted mass from paint is independent of temperature which means that bake‐out is expected to be successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The emission rate of VOCs depend on temperature and an increase in temperature will often lead to an increase in the emission rate [31][32][33]. The area-specific emission rates of formic acid and acetic acid from all investigated samples (no.…”
Section: The Impact Of Temperature and Rh On The Emission Of Formic Amentioning
confidence: 99%
“…The emission rate of VOCs depend on temperature and an increase in temperature will often lead to an increase in the emission rate [31][32][33]. The area-specific emission rates of formic acid and acetic acid from all investigated samples (no.…”
Section: The Impact Of Temperature and Rh On The Emission Of Formic Amentioning
confidence: 99%
“…Studies have reported 2EH emission from various sources, such as carpets, furnitures, computers, books, and food wrappings . Building materials, such as insulation and gypsum board, wallpaper, paint, PVC flooring, and adhesives, are also sources of 2EH emissions.…”
Section: Exposure Scenariomentioning
confidence: 99%
“…Numerous studies have researched volatile organic compounds (VOCs) in the field of wooden materials. Most studies have focused on the sampling and analysis method 2 – 4 , decorative properties 5 , 6 , release limit standard 7 , release characteristics 8 , and impact of environmental conditions 9 , 10 . However, the odor problem follows emission from materials, which may annoy a room’s occupants and impair their health.…”
Section: Introductionmentioning
confidence: 99%